PENGGUNAAN IEKAD DALAM BIMBINGAN KELOMPOK UNTUK MEMBANTU SISWA MEMAHAMI RENCANA PILIHAN KARIR - Citra Passa Hartadi; Syarifuddin Dahlan; Ratna Widiastuti (ALIBKIN (Jurnal Bimbingan Konseling), 2014)
The purpose of this research was to help students in understanding the plan of his career by using IEKAD in the group guidance. The problem in this research was that there were a lot of students who had difficulty in understanding the plan of career choices. The design used was a non randomized pre test post test control group. The subjects of research for the experimental and control group class of IPA as much as 31 students and for the experimental and control group class of IPS as much as 29 students. Data collection was using the scale of career choices understanding. The results of the research data with test-t on the experimental group in IPA class suggested that t calculate t table (12,77 2.00) and in IPS class showed that t calculate t table (8,13 2.00) so that Ha was accepted which meant that the understanding of career choices plan can be improved by using IEKADTujuan dalam penelitian ini adalah untuk membantu siswa memahami rencana karirnya dengan menggunakan IEKAD dalam bimbingan kelompok. Masalah dalam penelitian ini adalah banyak siswa yang mengalami kesulitan dalam memahami rencana pilihan karir. Desain yang digunakan adalah non randomized pre test-post test kontrol group. Subjek penelitian untuk kelas IPA kelompok eksperimen maupun kelompok kontrol sebanyak 31 siswa. Hal yang sama untuk kelas IPS kelompok eksperimen maupun kontrol sebanyak 29 siswa.Teknik pengumpulan data menggunakan skala pemahaman pilihan karir. Hasil penelitian data dengan uji-t pada kelompok eksperimen di kelas IPA menunjukkan bahwa t hitung t tabel ( 12,77 2,00 ) dan untuk kelas IPS menunjukkan bahwa t hitung t tabel (8,13 2,00) maka Ha diterima artinya pemahaman rencana pilihan karir dapat ditingkatkan dengan menggunakan IEKAD.Kata kunci : IEKAD, bimbingan kelompok, pilihan karir.